Inflammatory Cytokines, Endothelial Function, and Chronic Allograft Vasculopathy in Children: An Investigation of the Donor and Recipient Vasculature After Heart Transplantation. Issue 5 (2nd February 2016) - Fenton, M.; Simmonds, J.; Shah, V.; Brogan, P.; Klein, N.; Deanfield, J.; Burch, M.
Abstract : Chronic allograft vasculopathy (CAV) limits the lifespan of pediatric heart transplant recipients. We investigated blood markers of inflammation, endothelial dysfunction, and damage to both the native and transplanted vasculature in children after heart transplantation. Serum samples were taken from pediatric heart transplant recipients for markers of inflammation and endothelial activation. The systemic vasculature was investigated using brachial artery flow‐mediated dilatation and carotid artery intima‐medial hyperplasia. CAV was investigated using intravascular ultrasound. Mean intima‐media thickness (mIMT) > 0.5 mm was used to define significant CAV. Forty‐eight children (25 male) aged 8–18 years were enrolled in the study. Patients were a median (interquartile range) 4.1 (2.2–8.7) years after transplant. Patients had increased levels of circulating IL6 (3.86 [2.84–4.95] vs. 1.66 [1.22–2.63] p < 0.0001), vascular cell adhesion molecule 1 (539 [451–621] vs. 402 [342–487] p < 0.001), intracellular adhesion molecule 1 305 (247–346) vs. 256 (224–294) p = 0.002 and thrombomodulin (7.1 [5.5–8.1] vs. 3.57 [3.03–4.71] p < 0.0001) and decreased levels of tumor necrosis factor‐α, E selectin, and P selectin, compared with controls. The systemic vasculature was unaffected. Patients with severe CAV had raised serum von Willebrand factor and decreased serum thrombomodulin. Posttransplant thrombomodulin levels are elevated after transplant but significantly lower in those with mIMT > 0.5 mm. This suggests that subclinical inflammation is present and that natural anticoagulant/thrombomodulin activity is important after transplant. Abstract : Heart transplantation in children leads to an increase in inflammatory markers, endothelial activation and disruption of natural anticoagulant pathways, increasing the severity of cardiac allograft vasculopathy while having a negligible effect on the native vasculature.